2003
DOI: 10.3987/rev-02-561
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoid Coumarins of the Genus Ferula

Abstract: Chemical studies on the plants of the genus Ferula (Apiaceae) show the presence of many compounds belonging mainly to the groups of monoterpene coumarins, sesquiterpene coumarins, sesquiterpenes, furanocoumarins and aromatic compounds. Biological studies reveal significant activities, such as an anti-HIV activity, inhibition of cytokine release and early events of carcinogenesis. Extracts of some species of Ferula have long been used in folk medicine for treating various diseases, possess an antimicrobial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…A successful chemical survey of the roots of the F. lutea has contributed to the isolation of new dihydrofuranocoumarins, together with eight known compounds [6]. It is well known that the Ferula genus has a variety of coumarins [7], phenolics such as chlorogenic acid, gallic acid and pyrogallol [8]. Moreover, the Ferula genus is referred to be a good source of biologically active compounds like sesquiterpene derivatives [9,10], daucanes [11], germacranes [9] and sesquiterpene coumarins identified in the roots of the plants.…”
Section: Introductionmentioning
confidence: 99%
“…A successful chemical survey of the roots of the F. lutea has contributed to the isolation of new dihydrofuranocoumarins, together with eight known compounds [6]. It is well known that the Ferula genus has a variety of coumarins [7], phenolics such as chlorogenic acid, gallic acid and pyrogallol [8]. Moreover, the Ferula genus is referred to be a good source of biologically active compounds like sesquiterpene derivatives [9,10], daucanes [11], germacranes [9] and sesquiterpene coumarins identified in the roots of the plants.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports on the isolation of this compound from other Ferula families, e.g. Ferula persika, Ferula nevskia and Ferula iliensis (Abd El-Razek et al 2003), isolation of this compound in the present work was high so that using 10 g CHCl 3 extract resulted in the production of 80 mg compound 5.…”
Section: Resultsmentioning
confidence: 64%
“…The broad singlet resonance at d H 5.62 ppm (brs) was assigned to the olefinic hydrogen (H-7 0 ) in the 1 H NMR spectra. Although this compound was isolated from some other Ferula species such as Ferula concaula, Ferula korshinskyi, Ferula incisoserrata, Ferula foetidissima and Ferula sumbul (Abd El-Razek et al 2003), it has not yet been reported in F. assa-foetida and of course with a high yield.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous study dealing with members of this genus revealed that the main constituents are sesquiterpenes and sesquiterpene coumarins. More than 70 species have been studied chemically leading to the fact that germacranes, humulanes, carotanes, himachalanes, and guaianes represent the main sesquiterpene constituents of the genus [4-10]. Ferula spp.…”
Section: Introductionmentioning
confidence: 99%